VOSLI MUSTKY: THE BOOK OUT OF CONTEST - Novotny, Vladimir (Bohemica Olomucensia, 2020)
The text brings the author's biography of the regional writer Klara Gocarova and deals in detail with her trilogy Vosli mustky. It reveals the genre fusion and put Gocarova's texts in the context of tradition of humorous and memoir literature.
Keywords: humorous novel; regional literature; literary prizes; Klara Gocarova